The effect of in-process ethylene incorporation on the evolution of particle morphology and molecular characteristics of commercial heterophasic ethylene propylene copolymers (HEPCs) - Botha, Linda (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.